Routledge Philosophy GuideBook to Husserl and the Cartesian Meditations - Smith, A. D. (Routledge Philosophy GuideBooks, 2003)
Husserl is one of the most important philosophers of the twentieth century and his contribution to the phenomenology movement is widely recognised. The Cartesian Meditations is his most famous, and most widely studied work. The book introduces and assesses: Husserl's life and background to the Cartesian Meditations, the ideas and text of the Cartesian Meditations and the continuing imporance of Husserl's work to Philosophy.